Salivary aldosterone and cortisone respond differently to high- and low-psychologically stressful soccer competitions - McHale, T. S.; Chee, W.-C.; Hodges-Simeon, C. R.; Zava, D. T.; Albert, G.; Chan, K. C.; Gray, P. B. (Journal of Sports Sciences, 2020)
Aldosterone and cortisone are released in response to physical and psychological stress. However, aldosterone and cortisone responses in children engaged in physical competition have not been described. We examined salivary aldosterone and salivary cortisone responses among Hong Kongese boys, aged 8-11 years, during (1) a soccer match against unknown competitors (N = 84, high psychological stress condition) and (2) an intrasquad soccer scrimmage against teammates (N = 81, low psychological stress condition). Aldosterone levels increased during the soccer match and intrasquad soccer scrimmage conditions, consistent with the view that aldosterone responds to physical stress. During the soccer match, winning competitors experienced larger increases in aldosterone compared to losing competitors, indicating that the degree of aldosterone increase was attenuated by match outcome. Cortisone increased during the soccer match and decreased during the intrasquad soccer scrimmage. Competitors on teams that resulted in a tie had larger cortisone increases compared to winners or losers. These findings highlight that the degree of cortisone change is related to boy's cognitive appraisal of the competitor type (i.e., teammates vs. unknown competitors) and the competitive nature of the game (e.g., tie). These results shed new light on adrenal hormone mediators of stress and competition during middle childhood.